Portraits : the Hasidic legacy of Elie Wiesel - Patterson, David, 1948- (State University of New York Press, 2021)
"Explores Elie Wiesel's portraits of the sages of Judaism and elaborates on the Hasidic legacy from his life and his teaching"-- Provided by publisher
Keywords: Wiesel, Elie, -- 1928-2016 -- Criticism and interpretation.; Wiesel, Elie, -- 1928-2016; Hasidism.; Hassidisme.; LITERARY CRITICISM / Jewish.; Hasidism; Criticism, interpretation, etc.